Interaksi Sosial Lintas Agama Membangun Potensi Harmoni Anak di Perumahan PNS Kota Metro - Khumairo, Aisyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2019)
This study reveals the interfaith social interaction in building the harmony potential of children in Metro City civil servant housing. Community Housing PNS is a multicultural society that has a variety of religions, races, ethnicities and languages. In the midst of these differences becoming a force for the community, they assume that it can be a learning medium for children to get to know each other which then can grow the potential for social harmony in children from an early age, the community realizes that the environment is part from the second study room after the family for children. In their social interaction through two stages ranging from social contact to communication with each other. This research is a descriptive qualitative research field, the civil servant housing community is a place of research so the research uses a phenomenological approach in this study where data collection is done by observation, interviews and documentation. The results showed that the practice of interfaith social interaction developed by the community had a positive impact on children, the birth of the potential for social harmony in the souls of children in the environment.